Measuring the Ability of Poverty Alleviation Programs in Reducing Rural Poverty Levels in Eastern Indonesia - Muhammad Arif Prastyadi; I Wayan Suparta; Asih Murwiati (Jurnal Ekonomi Pembangunan, 2024)
Poverty is still a problem in many developing countries, including Indonesia, especially in eastern Indonesia, such as East Nusa Tenggara, Maluku, West Papua, and Papua. Based on Statistic Indonesia data, the poverty rate in the east of Indonesia shows a downward trend but is still well above the national average. This raises questions about the achievements of poverty alleviation programs. To overcome this problem, the government has created several programs to alleviate poverty. These programs include increasing social assistance, improving access to essential services, empowering communities, and promoting inclusive development. This study aims to measure the ability of poverty alleviation programs to reduce poverty levels in Eastern Indonesia. This study uses the Blundell-Bond System GMM (Sys-GMM) analysis technique to measure these programs' short-run and long-run effects. This study used secondary data from official institutions such as Statistics Indonesia and the Ministry of Finance of the Republic of Indonesia. The data collected includes the government budget for social assistance, average years of schooling, life expectancy, human development index, and Gini ratio. Based on the results obtained in this study during the research period from 2010 to 2022, it shows that (1) the government budget in the field of social protection as a proxy for social assistance programs has no significant effect on poverty, (2) the average length of schooling as a proxy for programs to improve access to essential services in the field of education has no effect on poverty, (3) life expectancy as a proxy for programs to improve essential services in the health sector significantly reduces poverty, community empowerment programs and inclusive development proxied by (4) the human development index has no significant effect on poverty, and (5) the Gini ratio has a significant effect on poverty.